Market Driven Product Ontologies - Meersman, Davor (Springer Lecture Notes in Computer Science, 2007)
In this paper we will introduce the concept of market driven product ontologies, which are used to incorporate market information into the knowledge system of a company as well as exchange it with other value cycle partners with minimal loss of information. In our vision, one would integrate market research output data with the ontological backbone of an organisation in such a way that it is relevant to every aspect of the product development process, thus permitting the information to travel deep down into the fibre of an organisation, contributing to product innovation, competence development and relevant social interaction. We will discuss early research challenges, issues and results, the anticipated research methodology and project pilot environment.